Distance educational technologies in teaching foreign languages (on the example of the Latin language) - Elena Vladimirovna Kiseleva (Вестник Майкопского государственного технологического университета)
The distance learning model is increasingly being introduced into the practice of educational institutions. Distance learning technologies allow the educational process to be carried out at a distance, expanding the capabilities of educational institutions. The research problem: the use of distance learning technologies in teaching Latin. The purpose of the research is to reveal the potential of distance learning technologies in teaching Latin. The research methods used are generalization, comparison, analysis, survey. The base of the research is FSBEI HE “Maykop State Technological University”, the Medical institute. The research results are the following: the potential of distance learning technologies in teaching Latin has been substantiated; studies related to the problem of distance learning in the study of foreign languages have been analyzed; the experience of using distance learning technologies in teaching Latin language has been presented. Key conclusions: distance learning technologies are information and communication technologies implemented using network resources in the indirect (distant) interaction between students and a teacher; distance learning technologies expand the possibilities of language training in modern conditions and can be considered as an additional resource for obtaining educational information, increasing the availability and quality of education; using e-Learning technologies (electronic educational environment of universities, Zoom and MIND online platforms) is an effective tool in teaching Latin, allowing to expand the range of opportunities for language training.